TWO CONCEPTS OF EMPIRICAL ETHICS - Parker, Malcolm (Bioethics, 2009)
The turn to empirical ethics answers two calls. The first is for a richer account of morality than that afforded by bioethical principlism, which is cast as excessively abstract and thin on the facts. The second is for the facts in question to be those of human experience and not some other, unworldly realm. Empirical ethics therefore promises a richer naturalistic ethics, but in fulfilling the second call it often fails to heed the metaethical requirements related to the first. Empirical ethics risks losing the normative edge which necessarily characterizes the ethical, by failing to account for the nature and the logic of moral norms. I sketch a naturalistic theory, teleological expressivism (TE), which negotiates the naturalistic fallacy by providing a more satisfactory means of taking into account facts and research data with ethical implications. The examples of informed consent and the euthanasia debate are used to illustrate the superiority of this approach, and the problems consequent on including the facts in the wrong kind of way.